Bulk density effects on soil hydrologic and thermal characteristics: A numerical investigation. Issue 14 (7th June 2018) - Kojima, Yuki; Heitman, Joshua L.; Sakai, Masaru; Kato, Chihiro; Horton, Robert
Abstract: Soil bulk density (ρb ) is commonly treated as static in studies of land surface dynamics. Magnitudes of errors associated with this assumption are largely unknown. Our objectives were to (a) quantify ρb effects on soil hydrologic and thermal properties and (b) evaluate effects of ρb on surface energy balance and heat and water transfer. We evaluated 6 soil properties, volumetric heat capacity, thermal conductivity, soil thermal diffusivity, water retention characteristics, hydraulic conductivity, and vapour diffusivity, over a range of ρb, using a combination of 6 models. Thermal conductivity, water retention, hydraulic conductivity, and vapour diffusivity were most sensitive to ρb, each changing by fractions greater than the associated fractional changes in ρb . A 10% change in ρb led to 10–11% change in thermal conductivity, 6–11% change in saturated and residual water content, 49–54% change in saturated hydraulic conductivity, and 80% change in vapour diffusivity. Subsequently, 3 field seasons were simulated with a numerical model (HYDRUS‐1D) for a range of ρb values. When ρb increased 25% (from 1.2 to 1.5 Mg m −3 ), soil temperature variation decreased by 2.1 °C in shallow layers and increased by 1 °C in subsurface layers. Surface water content differed by 0.02 m 3  m −3 for various ρb values during drying events but differences mostly disappeared in the subsurface. Matric potential varied by >100 m of water. Surface energy balance showed clear trends with ρb . Latent heat flux decreased 6%, sensible heat flux increased 9%, and magnitude of ground heat flux varied by 18% (with a 25% ρb increase). Transient ρb impacted surface conditions and fluxes, and clearly, it warrants consideration in field and modelling investigations.